HELMINTHS AND THEIR SPREAD, HELMINTH-CAUSED DISEASES (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The word "helminths" comes from the Greek meaning worm. The parasites that infect humans can be classified as heirlooms or souvenirs. Parasites that are inherited from ancestors in Africa are called Heirlooms, and those that are acquired from the animals during contact through our evolution, migrations, and agricultural practices are called souvenirs. In developing countries, the most common infectious agents of humans are these helminthic infections. More than a quarter of the world's population, that means approximately 2 billion people are affected by the helminthic parasite, and it is one of the major burdens of developing countries, especially in children.